The Effect of Low Power Ultrasonic Wave Exposure to Suppress Methicillin-Resistant Staphylococcus aureus (MRSA) In Vitro - Mansyur, Mas; Yudaningtyas, Erni; Prawiro, Sumarno Reto; Widjajanto, Edi (Journal of Tropical Life Science, 2018)
The incidence of methicillin-resistant Staphylococcus aureus (MRSA) infection keeps increasing in every part of the world. Currently, the infection prevalence of MRSA has reached 70% in Asia. In Indonesia in 2006 the prevalence was 23.5%; the infection prevalence of MRSA in RS Atmajaya Jakarta reached 47%, in RSUP Dr. Moh. Husin Palembang reached 46%, and RSUD Abdul Moeloek Lampung in 2013 reached 38.4%. MRSA is multiresistant to antibiotics and is hard to kill compared to most other negative gram bacteria. The purpose of this research is to find the lethal power and exposure of ultrasonic waves to kill MRSA, monitoring its ef-fects via changes in shape, size, structure and Gram staining as indicators. The observations were done mac-roscopically by culturing the MRSA in a petri dish filled with Chromagar MRSA medium, while the morpho-logical observations of MRSA were done by SEM, changes in the structure using TEM, and changes in the color of MRSA cells using Gram staining. Ultrasonic wave exposure, at a lethal power = 8.432 watt, killed a significant percentage of MRSA over the control (p = 0.000). The death indicators of the MRSA due to expo-sure to ultrasonic waves of various power were: changes in shape of MRSA affected by ultrasonic power (p = 0.005), changes in size is not affected by ultrasonic power (p= 0.470), the stain of MRSA cell staining from purple to pink affected by ultrasonic power (p = 0.000), all compared with the control. MRSA died due to ne-crosis, with physical evidence of the MRSA death such as mechanical stress marked by swollen MRSA cell, shift cell wall, crack and tears, cavitation marked by pieces of MRSA cell in the field of view due to explosions inside the cell, change to an irregular cell shape, and changes in color from black to transparent.